Neonatal screening for congenital hypothyroidism by measurement of plasma thyroxine and thyroid stimulating hormone concentrations. Issue 6488 (13th July 1985) - Griffiths, K D; Virdi, N K; Rayner, P H; Green, A
Abstract : Neonatal screening for congenital hypothyroidism was introduced in the City of Birmingham in 1980 by measuring concentrations of both thyroid stimulating hormone and thyroxine in plasma. Over two years 30 108 babies were tested. Thirty one babies were recalled because of thyroid stimulating hormone concentrations greater than 40 mU/l, of whom 12 were treated with replacement thyroxine. Six babies were found to have low thyroxine concentrations because of reduced thyroxine binding globulin and five raised thyroxine values because of increased thyroxine binding globulin. As a result of this study screening was continued with measurement of thyroid stimulating hormone only as the primary test for congenital hypothyroidism, the thyroxine value being measured only when the concentration of thyroid stimulating hormone exceeded 20 mU/l.